(untitled) (Global Journal of Human-Social Science, 2025)
The newsrooms of O Globo, Extra and Expresso were unified in 2017 in the so-called Integrated Newsroom, aiming to optimize production and expand focus on the digital environment. Eight years after the change, journalists working in Brazil´s largest news company evaluated the advantages and disadvantages of the process. As the main disadvantage, they pointed to the reduced attention given to newspapers in the so-called popular units. In this article, we analyze the interviews with the support of authors dedicated to studying the relationship between the accelerated pace of contemporary life and journalism, as well as the role of so-called sensation-driven journalism on the internet.